Synthesis of Kaolinite Nanotubes as Heterogeneous Catalysts for Transesterification Reaction of Waste Cooking Oil into Biodiesel - Muhammad Rizki; Fitri, Ernarisa; Syukri Arief; Rahadian Zainul; Syukri (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
Kaolinite, a naturally abundant clay mineral, possesses a significant surface area and catalytic properties. To enhance its catalytic efficiency, modification into kaolinite nanotubes is necessary, as this transformation increases surface area and porosity. The synthesis of kaolinite nanotubes was achieved through a solvothermal method, incorporating multiple intercalation and rolling processes influenced by ultrasonic waves, subsequently utilizing these nanotubes as heterogeneous catalysts. The resulting kaolinite nanotube catalysts exhibited well-defined nanotube morphology and were applied in the transesterification of waste cooking oil, with variations in methanol-to-oil ratios. The optimal biodiesel yield achieved was 49.84%, obtained after a 3-hour reaction period using a 3% w catalyst at 60 Â°C, with a methanol-oil ratio of 3:1. This research highlights the potential of kaolinite nanotubes as effective catalysts in biodiesel production.